2017
DOI: 10.1017/edp.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Retrain Attributions Using CBT: A Pilot Study

Abstract: The role of affective and cognitive factors in learning have long been recognised as imperative determinants of the learning process. Maladaptive styles with which we perceive and explain accomplishments and failures in achievement outcomes have an important motivational impact upon approach and avoidance behaviours towards academic tasks. Interventions to change these maladaptive styles are well established, although they stand to gain via addition of cognitive behavioural therapy components. A pilot study at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…By their very definition labelling students with terms which can be regarded as being negative can affect teachers attitudes to inclusion of students with various levels of need (Kraska & Boyle, 2014;Boyle & Sharma, 2015, Anderson &, 2015. There are various programmes in schools which were initially designed mainly to support students with SEN, however it was found that in a mainstream environment they were just as effective as they enhanced confidence and self-esteem irrespective of difficulty (Bosnjak et al, 2017;Chodkiewicz & Boyle, 2014, 2016Koles & Boyle, 2013). Extra provisions can be provided even without terms like 'special needs' and 'children and young people with SEN'.…”
Section: How Do Sen Labels Affect Discrimination Stigmatisation and E...mentioning
confidence: 99%
“…By their very definition labelling students with terms which can be regarded as being negative can affect teachers attitudes to inclusion of students with various levels of need (Kraska & Boyle, 2014;Boyle & Sharma, 2015, Anderson &, 2015. There are various programmes in schools which were initially designed mainly to support students with SEN, however it was found that in a mainstream environment they were just as effective as they enhanced confidence and self-esteem irrespective of difficulty (Bosnjak et al, 2017;Chodkiewicz & Boyle, 2014, 2016Koles & Boyle, 2013). Extra provisions can be provided even without terms like 'special needs' and 'children and young people with SEN'.…”
Section: How Do Sen Labels Affect Discrimination Stigmatisation and E...mentioning
confidence: 99%
“…Because cognitive style is associated with other mental health problems, such intervention could lead to broader benefits. There is evidence that cognitive style can be altered using cognitive behavioural therapy (CBT) [49, 50], and that CBT for other mental disorders also reduces problem drinking [51, 52]. There is, therefore, scope for people seeking help for alcohol problems to target their negative cognitive style using CBT, so that they engage in healthier coping behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Because cognitive style is associated with other mental health problems, such intervention could lead to broader benefits. There is evidence that cognitive style can be altered using cognitive behavioural therapy (CBT) [49,50], and that CBT for other mental disorders also reduces problem drinking [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The concepts of 'self-esteem' and 'self' is very important in education as a belief in one's own ability and therefore successful attribution can enhance ability to complete task requirements (Bosnjak, Boyle, & Chodkiewicz, 2017 Koles & Boyle, 2013). Carl Rogers (1995) explains the self as one's experience or image of oneself.…”
Section: Accepted For Publication In Special Issue (Labelling and Dia...mentioning
confidence: 99%